Features of distribution of soybean agglutinin (sba) receptors in the extracellular matrix of the menisci of rat knee joint after intrafetal injection of antigens - Abrosimov, Yu. Yu.; Абросімов, Юрій Юрійович (publishing center of the ESCBM, The Czech Republic, 2019)
The results of previous investigations at the Department of Human Anatomy of Zaporizhzhia State Medical University have shown that intrafetal injection of antigens leads to changes in the rates of morphogenesis of fetal organs and tissues, that can be used for the modeling of the syndrome of undifferentiated connective tissue dysplasia in rats [3]. Lectins are informative molecular probes that can detect glycoconjugates in cells and tissues. Lectins and their receptors provide extracellular, cell-matrix interactions, participate in the regulation of proliferation, differentiation and apoptosis of cells [1, 2]. Previously we have shown that distribution of the receptors to other lectins (WGA, VSA) differs in intact knee joint menisci and after intrauterine antigenic effect [4, 5]. Aim of the work was to establish the features of distribution of Soybean agglutinin (SBA) receptors in the extracellular matrix of the menisci of rat knee joint after intrafetal injection of antigens.
Keywords: meniscus; rat; antigen; Soybean agglutinin (SBA)